2012
DOI: 10.1007/s10165-012-0717-7
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus and methotrexate-related CNS lymphoma in a patient with rheumatoid arthritis

Abstract: Patients with rheumatoid arthritis (RA), especially those treated with methotrexate (MTX), might have an increased risk of lymphoproliferative disorders that are associated with Epstein-Barr virus (EBV). We describe a case of EBV-associated central nervous system (CNS) lymphoma (diffuse large B-cell lymphoma) in a patient with RA on a short course of MTX treatment. The neoplastic cells express the B-cell surface markers (CD20, Pax-5 and CD30), and EBV-encoded RNA was demonstrated by in situ hybridization. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Of the eight cases of cerebral MTX-LPD, seven (including our case) presented as multiple lesions; only one case presented as a solitary lesion. 7 , 8 , 10 , 11 , 13 15) One case with medullary LPD presented with a solitary mass, 9) and a case with hypertrophy of the dura mater presented as intravascular large B-cell lymphoma (IVLBCL). 12) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the eight cases of cerebral MTX-LPD, seven (including our case) presented as multiple lesions; only one case presented as a solitary lesion. 7 , 8 , 10 , 11 , 13 15) One case with medullary LPD presented with a solitary mass, 9) and a case with hypertrophy of the dura mater presented as intravascular large B-cell lymphoma (IVLBCL). 12) …”
Section: Discussionmentioning
confidence: 99%
“…Other immune suppressors, such as adalimumab, bucillamine, etanercept, and prednisolone, were used in four primary CNS MTX-LPD cases. 9 , 11 , 12 , 14) …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Migita et al also reported a patient with RA who developed an EBV-related PCNSL during treatment with MTX. They underwent surgical resection and MTX withdrawal, resulting in MTX-LPD improvement without any recurrence [ 18 ].…”
Section: Discussionmentioning
confidence: 99%